Peran Komunikasi Keluarga dalam Pengambilan Keputusan Mahasiswa Asing untuk Kuliah di Indonesia - Neva Halwa Khairunissa; Lucy Pujasari Supratman (Universitas Tarakanita, 2024)
Studying abroad is something that many students want to do. However, it is clear that a serious decision requires careful consideration including considering the viewpoints of family members. This study aims to determine the role of family communication in international students' decision-making in discussing their desire to study abroad. This research uses qualitative methodology and a case study approach. As a result, both families and international students recognized the importance of family contact in the decision-making process of international students. Family communication allows for expressing opinions and listening to perspectives, which ultimately leads to mutual agreement and understanding among international students and their families.